Nilai-Nilai Kearifan Lokal Melalui Tari Galombang Gaya Sasaran: Studi Sasaran Sebagai Sarana Pendidikan Kultural - Nerosti Nerosti (Dance and Theatre Review, 2019)
This article aims to discuss the issue of Minangkabau local wisdom manifested in Galombang dance activities in the context of the target style. The existence of pencak silat targets is very meaningful for Minangkabau men because the target is not only a means of physical endurance training but also a basis for cultural education for Minangkabau people. Thus, the problem that will be expressed in this article is about the importance of the target for men in Minangkabau as a means of educating local wisdom, by expressing the implementation of local wisdom values through the target-style Galombang dance, and also explaining the extent to which values of the local wisdom is manifested in today’s Galombang dance performances. Sasaran and Galombang dance are two things that are interconnected in building the values of local wisdom in Minangkabau. This cultural activity has been started since the past when the royal system ruled in Minangkabau. In turn, the target as a forum for cultural education that contains local wisdom values becomes the place to produce Galombang dance, so that the values of local wisdom are manifested in the target-style Galombang dance.Keywords: local wisdom values; Sasaran; Sasaran Style of Galombang dance